Association of Smoking, Alcohol Use, and Betel Quid Chewing with Epigenetic Aberrations in Cancers - Wang, Tong-Hong (Int J Mol Sci, 2017)
Numerous environmental factors such as diet, alcohol use, stress, and environmental chemicals are known to elicit epigenetic changes, leading to increased rates of cancers and other diseases. The incidence of head and neck cancer, one of the most common cancers in Taiwanese males, is increasing: oral cancer and nasopharyngeal carcinoma are ranked fourth and tenth respectively, among the top ten cancers in this group, and a major cause of cancer-related deaths in Taiwanese males. Previous studies have identified smoking, alcohol use, and betel quid chewing as the three major causes of head and neck cancers; these three social habits are commonly observed in Taiwanese males, resulting in an increasing morbidity rate of head and neck cancers in this population. In this literature review, we discuss the association between specific components of betel quid, alcohol, and tobacco, and the occurrence of head and neck cancers, lung cancer, gastrointestinal cancers, and urethral cancer. We focus on regulatory mechanisms at the epigenetic level and their oncogenic effects. The review further discusses the application of FDA-approved epigenetic drugs as therapeutic strategies against cancer.